2022
DOI: 10.3389/fimmu.2022.861885
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis and the Risk of Cardiovascular Diseases: A Mendelian Randomization Study

Abstract: BackgroundObservational studies suggested that multiple sclerosis (MS) is associated with cardiovascular diseases (CVDs). However, the causal association has not been fully elucidated. Thus, we aim to assess the causality of the associations of MS with risk of CVDs.MethodsA two-sample Mendelian randomization (MR) study was performed to explore the causality. Genetic instruments were identified for MS from a genome-wide association study (GWAS) involving 115,803 individuals. Summary-level data for CVDs were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Recent evidence suggests that MS may directly cause some comorbidities, as identified using Mendelian randomization methods. One study suggested a causal effect of MS on lung cancer (odds ratio [OR] 1.07, p=0.0082) ( 19 ) and cardiovascular diseases, including IHD (OR 1.02, p=0.03) and myocardial infarction ( 25 , 26 ), but conflicting evidence for stroke ( 25 , 26 ). These findings are consistent with observations that the increased risk of IHD in persons with MS is not fully explained by traditional vascular risk factors ( 11 ).…”
Section: Etiology Of Comorbiditymentioning
confidence: 99%
“…Recent evidence suggests that MS may directly cause some comorbidities, as identified using Mendelian randomization methods. One study suggested a causal effect of MS on lung cancer (odds ratio [OR] 1.07, p=0.0082) ( 19 ) and cardiovascular diseases, including IHD (OR 1.02, p=0.03) and myocardial infarction ( 25 , 26 ), but conflicting evidence for stroke ( 25 , 26 ). These findings are consistent with observations that the increased risk of IHD in persons with MS is not fully explained by traditional vascular risk factors ( 11 ).…”
Section: Etiology Of Comorbiditymentioning
confidence: 99%
“…For each study, further details of definitions used to assess heart failure status have been published previously [15] (Supplementary Table S2, http://links.lww.com/HJH/C74). The GWAS was used in many Mendelian randomization studies [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…The GWAS [15] (Supplementary Table S2, http://links.lww.com/HJH/C74). The GWAS was used in many Mendelian randomization studies [23,24].…”
Section: Data For Heart Failurementioning
confidence: 99%
“…Still, the recent finding establishes a strong association with cardiovascular diseases like myocardial infarction, heart failure, atrial fibrillation, and ischemic stroke. 33 As a pivotal contributor to cardiovascular impairments, the blood platelets significantly modulate the pathophysiology of MS. For example, an increased number of hyperactivated platelets expressing surface exposure of P-selectin are observed in the demyelinating lesions of the inflamed brain and spinal cord of MS patients. 15 Activated platelets in the brain may provide an additional source for the production of reactive oxygen species (ROS) as well as reactive nitrogen species (RNS).…”
Section: Role Of Platelet In Msmentioning
confidence: 99%